The Role of International Law in the Resolution of Boundary Disputes in Africa: A Case Study of Bakassi Peninsula - Abdulyakeen, Abdulrasheed (Universitas Muhammadiyah Yogyakarta, 2022)
This paper investigates how international law helped Nigeria and Cameroon settle their territorial dispute over the Bakassi Peninsula from 1999 to 2008. The study utilized the case study research design with a qualitative approach which enabled data to be derived from various sources, including documentary records and semi-structured elite interviews. The findings showed that the ICJ’s ruling in October 2002 did not address urgent and immediate compliance. All subsequent attempts at arbitration were guided by the law established by the dispute resolution in the form of an award. Every diplomatic tactic employed was modified to follow the court’s ruling, resulting in a peaceful conclusion of the conflict and enhancing the continued importance of law in international interactions between states.